More about post-transplant cyclophosphamide in haploidentical grafts: full or reduced doses? - Moisés Manuel Gallardo-Pérez; César Homero Gutiérrez-Aguirre; Juan Carlos Olivares-Gazca; Guillermo José Ruiz-Argüelles (Hematology)
Haploidentical hematopoietic can be conducted on an outpatient basis but the two main reasons to accept into the hospital a patient in this setting are complications of the hematological toxicity and/or the cytokine-release syndrome. With the aim of reducing the post-transplant cyclophosphamide-dependent toxicity without compromising its effectivity, attempts to reduce the dose of post-transplant cyclophosphamide have been made: Decreases from the conventional total dose of post-transplant cyclophosphamide (100 mg/Kg) have been explored worldwide, showing that decreasing the total dose to even 50 mg/Kg significantly decreases the toxicity of the procedure without compromising its efficacy, safety and results. We present here the salient data of the attempts to diminish the doses of post-transplant cyclophosphamide which have been done and published worldwide, information that suggests that the conventional doses of post-transplant cyclophosphamide can be significantly reduced thus decreasing the toxicity, without compromising the effectiveness of the procedure, mainly the development of graft versus host disease.